The Relationship Between Family Support and the Application of Parenting Patterns - Ina Agustina; B. Kedang Sabinus; Yulianti Kristiani Banhae (Indonesian Journal of Global Health Research, 2022)
Good parenting patterns receive less attention from the community, especially farming communities with low economic levels, education levels and insight into the growth and development of children. From preliminary data, there are some parents in Kuanheun village who say "stupid child", "bad child" when their children do not obey their orders. The majority of Kuanheun villagers work as farmers. This study aims to determine the relationship between family support and upbringing in the farming community of Kuanheun village. The research design is analytic observational, cross-sectional design. This research was conducted in Kuanheun Village, West Kupang District in August - October 2019. The population was all mothers under five in Kuanheun Village, West Kupang District, totaling 91 people. The sampling technique was non-probability sampling/non-random sampling, totaling 91 people. Simple linear regression statistical test, the result, p: 0.194 or <0.005 (not significant). Descriptively, the family support for parenting was mostly good, namely 39 respondents (42.8%), the application of parenting was mostly quite good, namely 72 respondents (79.1%). Conclusion: there is no relationship between family support and the implementation of childcare in the farming community of Kuanheun village.